2010
DOI: 10.1007/s00277-010-0926-0
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant statin use does not impair the clinical outcome of patients with diffuse large B cell lymphoma treated with rituximab-CHOP

Abstract: Preclinical data indicated a detrimental effect of statins on the anti-lymphoma activity of rituximab. We evaluated the impact of concomitant statin medication on the response and survival of patients with diffuse large B cell lymphoma (DLBCL) receiving rituximab-cyclophosphamide, doxorubicin, vincristine, prednisone (R-CHOP) as first-line therapy. Medical histories of patients with DLBCL who were treated with R-CHOP as first-line therapy were assessed for concomitant statin use, response after completion of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 26 publications
(28 reference statements)
1
19
0
Order By: Relevance
“…Nevertheless, a recent cohort study involving patients with diffuse large B cell lymphoma (DLBCL) treated with CHOP and rituximab (R-CHOP) and concurrent statin use showed a 5-year event-free survival (EFS) of 67.3 % in patients without statin use compared with 79 % of patients receiving statins during R-CHOP (hazard ratio [HR], 0.47; 95 % CI, 0.15-1.54). The overall survival (OS) at 5 years was 81.4 % for patients without statin use compared with 93.3 % in the statin group (HR, 0.58; 95 % CI, 0.07-4.55), thus dismissing any detrimental impact of concurrent statin use during R-CHOP treatment in terms of EFS and OS [96]. Another large prospective cohort study of newly diagnosed patients with DLBCL and follicular lymphoma (FL) found that concomitant use of a statin in rituximabtreated patients had no impact on the overall response rate and survival.…”
Section: Rituximabmentioning
confidence: 97%
“…Nevertheless, a recent cohort study involving patients with diffuse large B cell lymphoma (DLBCL) treated with CHOP and rituximab (R-CHOP) and concurrent statin use showed a 5-year event-free survival (EFS) of 67.3 % in patients without statin use compared with 79 % of patients receiving statins during R-CHOP (hazard ratio [HR], 0.47; 95 % CI, 0.15-1.54). The overall survival (OS) at 5 years was 81.4 % for patients without statin use compared with 93.3 % in the statin group (HR, 0.58; 95 % CI, 0.07-4.55), thus dismissing any detrimental impact of concurrent statin use during R-CHOP treatment in terms of EFS and OS [96]. Another large prospective cohort study of newly diagnosed patients with DLBCL and follicular lymphoma (FL) found that concomitant use of a statin in rituximabtreated patients had no impact on the overall response rate and survival.…”
Section: Rituximabmentioning
confidence: 97%
“…Concerns have been raised since the publication of an experimental study that demonstrated a possibly impaired effect of rituximab treatment by statin use [18]. Clinical studies [19][20][21][22][23][24]36,57,58], all with a very small number of patients, tried to verify this finding in patients and have produced mixed findings. Our analysis did not show any impact of statin use on NHL progression or survival.…”
mentioning
confidence: 99%
“…[2][3][4] In this regard, it provides an additional validation of previous studies indicating that concurrent statin use does not affect the clinical efficacy of rituximab and rituximabcontaining therapy. [2][3][4] In this regard, it provides an additional validation of previous studies indicating that concurrent statin use does not affect the clinical efficacy of rituximab and rituximabcontaining therapy.…”
mentioning
confidence: 64%